2014
DOI: 10.1002/jso.23727
|View full text |Cite
|
Sign up to set email alerts
|

Low-heat treated autograft versus allograft for intercalary reconstruction of malignant bone tumors

Abstract: Our data suggest that intercalary allograft has better survival and fewer complications than the low-heat treated autograft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 16 publications
2
25
2
Order By: Relevance
“…24 Although there were only a few studies regarding the outcomes of intercalary reconstruction with heat-treated autografts, the nonunion rate (38%) and mean time to union (14.0 months) in our series were similar to those in previous reports of intercalary reconstruction with heat-treated autografts. 5,24 Allografts have been widely used for intercalary reconstruction of Additionally, a recent study in the Netherlands reported that the nonunion rate in patients who received intercalary allograft reconstruction was 40% (35 of 87 patients). 4 Based on these results, the nonunion rates reported for allograft reconstruction seemed to be comparable with that in our study using intercalary heat-treated autografts.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…24 Although there were only a few studies regarding the outcomes of intercalary reconstruction with heat-treated autografts, the nonunion rate (38%) and mean time to union (14.0 months) in our series were similar to those in previous reports of intercalary reconstruction with heat-treated autografts. 5,24 Allografts have been widely used for intercalary reconstruction of Additionally, a recent study in the Netherlands reported that the nonunion rate in patients who received intercalary allograft reconstruction was 40% (35 of 87 patients). 4 Based on these results, the nonunion rates reported for allograft reconstruction seemed to be comparable with that in our study using intercalary heat-treated autografts.…”
Section: Discussionsupporting
confidence: 86%
“…The rates of fracture (4%) and infection (13%) in our series were comparable with those reported previously. Functional outcomes in the present study showed a comparable MSTS score, with a mean value of 76%, to those reported in the literature regarding intercalary reconstruction using heat‐treated autografts or allografts, which ranged from 70% to 90% . The potential risk of local recurrence was a concern related to the recycling technique of the tumor‐bearing bones.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations